Performance of air plasma sprayed Cr3C2–25NiCr and NiCrMoNb coated X8CrNiMoVNb16–13 alloy subjected to high temperature corrosion environment. (27th January 2022) - Subramani, P; Sathishkumar, M; Manikandan, M; Selvaraj, Senthil Kumaran; Sreenivasulu, V; Arivazhagan, N; Rajkumar, S
Abstract: Thermal barrier coating plays a vital role in protecting materials' surfaces from high-temperature environment conditions. This work compares the demeanour of uncoated and air plasma sprayed Cr3 C2 –25NiCr and NiCrMoNb coated X8CrNiMoVNb16–13 substrates subjected to air oxidation and molten salt (Na2 SO4  + 60%V2 O5 ) environment condition at 900 °C for 50 cycles. Coating characteristics have been analyzed through microstructure, thickness, porosity, hardness, and bond strength. SEM, EDS and XRD analysis were used to analyze corrosion's product at the end of the 50th cycle. Coating microstructures showed a uniform laminar structure that is adherent and denser with a coating thickness of 150 ± 20 μ m and porosity less than 3.5%. The Microhardness of both the coated substrates were higher than that of the bare substrate. Cr3 C2 –25NiCr and NiCrMoNb coating bond strength was 38.9 MPa and 42.5 MPa. Thermogravimetric analysis showed the parabolic rate law of oxidation for all the substrates in both environments. In the molten salt environment, all the substrates exhibited higher weight gain compared to the air oxidation environment. In both environmental conditions, the uncoated X8CrNiMoVNb16–13 alloy exhibited higher weight gain than the coated substrates. The formation of Cr2 O3, NiO and spinel oxide NiCr2 O4 offers good resistance to corrosion to all the substrates in both the environmental condition. However, the presence of Mo and Nb significantly accelerated the corrosion of the substrate, thereby increasing the weight of the NiCrMoNb substrate. It is observed that Cr3 C2 –25NiCr and NiCrMoNb coating over the X8CrNiMoVNb16–13 substrate significantly protected the substrate against the hot corrosion than the bare alloy exposed to similar environmental conditions.